Supportive leadership and employee creativity: Will Leader-Member Exchange mediate the relationship? - Dwinanda Jalu Prasetya Prinhandaka; Isnanda Zainur Rohman; Nikodemus Hans Setiadi Wijaya (Annals of Management and Organization Research, 2022)
Purpose: Purpose: This study proposes to integrate supportive leadership, leader-member exchange (LMX), and employee creativity. It suggests that LMX can play a role as a mediator. Research methodology: A total of 200 participants were included in this study. They were working for a tobacco company located in a district in Kulon Progo, Yogyakarta, Indonesia. Analysis for hypotheses was done in SPSS and AMOS. Results: It was found that supportive leadership was positively related to leader-member exchange (LMX) and employee creativity. Leader-member exchange (LMX) was positively related to employee creativity. Finally, leader-member exchange (LMX) mediated the relationship between supportive leadership and employee creativity. Limitations: The participants of this study were taken from one company. This might lower the generalizability of the results. Another limitation of this study is the use is a cross-sectional method in the data collection which might result in a common method variance. Future studies could employ other data collection methods. For example, a multi-wave of data collection can remedy the problem. Contribution: The study suggests that a supportive leadership style is necessary to implement because it can promote a higher quality of the relationship between employees and their supervisors. More importantly, this aligns with the organizational effort to foster employee creativity. Novelty: The study found that supportive leadership can promote leader-member exchange (LMX) quality. Since the dyad relationship quality characterized by leader-member exchange (LMX) is necessary for team effectiveness, the investigation of the link may provide an understanding of the factors that may influence leader-member exchange (LMX).